2005
DOI: 10.1111/j.1600-0420.2005.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of lacrimal gland tissue outside the lacrimal fossa: comparison of clinical and histopathological findings

Abstract: ABSTRACT.Purpose: To analyse clinical referral diagnoses and the location of lesions with histologically verified lacrimal gland tissue occurring outside the fossa of the lacrimal gland. Methods: Sections of lesions excised from areas outside the fossa of the lacrimal gland containing lacrimal gland tissue on histological examination were collected from the files of the Eye Pathology Institute, Copenhagen, Denmark. Specimens spanned a period of 50 years. Sections were re-examined and referral data on location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…Ectopic lacrimal gland tissue is a rare histologic finding that most commonly affects the bulbar conjunctiva and limbus. 5 It has also been described in the eyelid, conjunctiva, sclera, cornea, iris, choroid, and orbit. 6 It can present either as an isolated choristoma, or as a complex choristoma also containing cartilage, nerve, or be located within a dermolipoma, as was found in the described case.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Ectopic lacrimal gland tissue is a rare histologic finding that most commonly affects the bulbar conjunctiva and limbus. 5 It has also been described in the eyelid, conjunctiva, sclera, cornea, iris, choroid, and orbit. 6 It can present either as an isolated choristoma, or as a complex choristoma also containing cartilage, nerve, or be located within a dermolipoma, as was found in the described case.…”
Section: Discussionmentioning
confidence: 97%
“…In their study, they found that most cases (38, 62%) were complex choristomas, while 23 cases (38%) represented isolated ectopic lacrimal gland tissue. 5 All of the cases were located temporally, with 48 cases (79%) in the temporal epibulbar conjunctiva, and 13 cases (21%) located in the temporal orbit outside the lacrimal fossa. 5 To our knowledge, the described case may represent the first description of ectopic lacrimal gland occurring in the medial orbit deep in the inferomedial conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lacrimal apparatus comprises of the main lacrimal gland and the two sets accessory glands (of Krause and of Wolfring). While the main lacrimal gland is situated in the orbital lacrimal fossa, its palpebral lobe is situated on the temporal side of the superior fornix [1]. Whilethe eyelids [2], tarsal plate [3] and the nasal mucosa [4] have been reported to harbor ectopic lacrimal gland tissue, the commonest sites involved are the bulbar conjunctiva and limbal area [5,6].…”
Section: Introductionmentioning
confidence: 99%